Phase II study of S-1 in patients with previously-treated invasive thymoma and thymic carcinoma: North Japan lung cancer study group trial 1203. (January 2020) - Tsukita, Yoko; Inoue, Akira; Sugawara, Shunichi; Kuyama, Shoichi; Nakagawa, Taku; Harada, Daijiro; Tanaka, Hisashi; Watanabe, Kana; Mori, Yoshiaki; Harada, Toshiyuki; Hino, Toshihiko; Fujii, Masanori; et al.
Highlights: This is the first phase II trial to evaluate S-1 in thymoma and thymic carcinoma (TC). S-1 had a clinical benefit for TC similar to immunotherapies but at lower cost. The toxicity profile was acceptable. S-1 monotherapy could represent a treatment option for TC. Abstract: Objectives: Invasive thymoma (IT) and thymic carcinoma (TC) are rare epithelial neoplasms arising in the anterior mediastinum. Platinum-based chemotherapies are widely used for first-line treatment of unresectable IT and TC, but no standard treatment has been established for previously-treated IT and TC thus far. Because promising efficacy of S-1 (tegafur, gimeracil and oteracil combination) has been reported in some retrospective studies, we conducted the first prospective phase II trial to evaluate its efficacy in previously-treated patients with advanced IT and TC. Materials and Methods: Patients progressing after at least one regimen of systemic chemotherapy received S-1 orally at a dose based on body surface area for 2 weeks followed by one week of rest until tumor progression or unacceptable toxicity. The primary endpoint was overall response rate (ORR) and secondary endpoints were progression-free survival (PFS), overall survival (OS), and toxicity profile. We defined an ORR of 25% as indicating potential usefulness while ORR of 10% was the lower limit of interest. Results: Forty patients were enrolled (IT, n = 20; TC, n = 20). ORR was 17.5% (95% CI 7.3–32.8; IT, 10%; TC, 25%), disease control rate was 85% (IT, 95%; TC, 75%). Median PFS was 7.0 months (IT, 11.3 months; TC, 5.4 months), and median OS was 40.3 months (IT, 58.5 months; TC, 22.7 months) with a median follow-up of 51.9 months. Major toxicities (grade 3–4) were anorexia (10%), neutropenia (7.5%) and pneumonitis (5%). No treatment-related death was observed. Conclusion: Although the primary endpoint was not met, S-1 monotherapy did have effects similar to recently reported immunotherapies for TC but at much lower cost. S-1 could represent a treatment option for previously-treated advanced TC. This trial was registered as UMIN 000008174.